Pathogen Inventory of Botia (Chromobotia macracanthus Bleeker) in Fish Quarantine Supadio, Pontianak - Ristyana Dewi Herawati (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2015)
Disease was a major obstacle in the cultivation of orrnamental fish, one of them is botia. The many types of diseases that infected botia can cause huge losses. The efforts that could minimize these losses was prevented the spread of disease. The purpose of this study was to determine the types of pathogen that infected botia (Chromobotia macracanthus Bleeker) in fish quarantine Supadio, Pontianak. The observations were identification of parasites, bacteria and fungi. The results showed that the agent of disease affecting botia are Gyrodactylus sp., Myxobolus sp., Argulus sp., Vorticella sp. from parasite agent, Neisseria sp., Aeromonashydrophila, Chromobacterium violaceum, Pasteurella hemolytica from bacteria agent and Saprolegnia sp. from fungi agent. All of agent diseases are not belonged to fish disease quarantine.